A new static cost-effective parameter for interconnection networks of massively parallel computer systems - Hafizur Rahman, M. M.; Ali, Mohammed N.M.; Ibrahim, Adamu Abubakar; Behera,, Dhiren Kumar; Miura, Yasuyuki; Inoguchi, Yasushi (Springer Nature, 2018)
The increasing of the signaling technology motivated the research community to find alternative solutions to replace the sequential computing systems. These systems reached their limits, and it became an infeasible choice to manage the computational grand challenges. Thereby, many types of research have been conducted to improve a system with special characteristics able to cope with the new technology. Massively parallel computer (MPC) systems have been emerged to solve the complex computing challenges in parallel and concurrently. The performance of these systems is affected by the structure of the underlying interconnection network. Therefore, many designs of interconnection networks topologies have been presented looking for an optimal one. In this paper, we present the architecture of MMN which is a hierarchical interconnection network. The static and dynamic performance parameters of MMN have been evaluated in previous studies, and it provided good results compared to the conventional interconnection network topologies. This paper will focus on evaluating and determining the static cost-effective parameter of MMN which is the product of the relation between the node degree, network diameter, wiring complexity, and the total number of nodes in each network.